Technological Monitoring of Cagaita (Eugenia dysenterica) and Potential Biotechnological Applications - Rodrigues-Silva, Paolo Lucas (2021)
The savannah biome occupies about 23% of Brazil’s surface area, considered the second largest biome in Brazil. It has about 4,800 endemic species, including the fruiting species Eugenia dysenterica DC. (cagaita tree). Rich in nutrients, this species has economic potential in Brazil, as it has actions directly related to human health. This study carried out technological monitoring on the knowledge and technologies generated, using the species E. dysenterica, over the period of 2009-2019. Data showed that for this species 77 master theses, 21 doctoral theses, 97 scientific manuscripts, and two patents were found during this period. A more detailed analysis showed that part of the knowledge and technologies generated is concentrated in the field of environmental biotechnology (35.9%), followed by industrial biotechnology (28.3%), health biotechnology (22.8%), and plant biotechnology (13%). Thus, the potential to be explored in relation to E. dysenterica for the development of biotechnological products of commercial interest is discussed.